Dexter’s and Emma’s Defense Mechanisms which Contribute to Complicated Love Relationship in David Nicholls’ One Day - ALIT MAHARDIKA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Psikologimenjadihal yang sangatpentingketikaditerapkandalammenganalisatokohdalam novel. Hal yangpentingadalahbagaimanatokoh-tokohmenghadapi plot, dansewaktu-waktumerekaharusmenghadapisesuatu yang takdapatditerima, halinimemicumunculnyakecemasan yang berakhirpadamekanismepertahanan ego. Hal inilah yang dialami Dexter dan Emma, mekanismepertahanan ego merekamemainkanperasaanmerekadalamsebuahikatan, ikatancinta.Berdasarkanfaktatersebut, rumusanmasalah yang dapatdiambiladalah (1) bagaimanamekanismepertahanan ego terpaparkanpadadiri Dexter dan Emma dalam novel One Day karya David Nicholls? (2) bagaimanamekanismepertahanan ego tersebutmempengaruhihubunganantaradexterdan Emma dalam novel One Day karya David Nicholls? Sedangkantujuandanmanfaatpenelitiansecaraotomatisakanmenjawabmasalah-masalah yang sudahdimunculkan. Untukmenjembatanibagian yang sulitdalamanalisaini, penggunanmetodemengerucutpadainterpretasiyangmenggunakanteknikpengumpulandatadenganakibatsecarapsikologis, sedangpendekatannyamenggunakanpendekatanobjektif.Analisaakanmengacupadaduatokohutama, Dexter dan Emma, dimanamekanismepertahanan ego merekamemisahkansekaligusmenyatukancintamereka, sehinggahalinimenjadijelasbahwamekanismepertahanan ego selainmengakibatkankonflik internal, jugamempengaruhikonflikdalamhubungandengan orang lain.Keywords: Psikologi, mekanismepertahanan egokonflik, danhubungan.AbstractPsychology becomes the crucial thing when it is used to analyze characters in novel. The important thing is how the characters face the plots, and sometimes they have to face something cannot be accepted, these are sourced to them of getting anxiety that ends to defense mechanism. This is what Dexter and Emma have to face, their defense mechanisms play on their relation, especially love. Based on those facts, the problems are (1) how are defense mechanisms depicted in DexterandEmmain David Nichollis‟ One Day? (2) how do defense mechanisms affect to the relation between Dexter and Emma in David Nichollis‟ One Day?And the objectives and significances automatically follow it. To bridgethe hard part in the analysis, the used method is interpretation that uses techniqueconnecting data with the impact psychologically and the approach is objective. Based on the analysis goes further with the two characters, Dexter and Emma,they have defense mechanisms that can separate them and also unite them, thus it can be clear to get that defense mechanism besides influencing their own psychology conflict, also influences their relation to each other.Keywords: Psychology, defense mechanism, conflict, and relation.